Heparan Sulfate: A Potential Candidate for the Development of Biomimetic Immunomodulatory Membranes - Corradetti, Bruna; Taraballi, Francesca; Giretti, Ilaria; Bauza, Guillermo; Pistillo, Rossella S.; Banche Niclot, Federica; Pandolfi, Laura; Demarchi, Danilo; Tasciotti, Ennio (Frontiers in Bioengineering and Biotechnology, 2017)
Clinical trials have demonstrated that heparan sulfate (HS) could be used as a therapeutic agent for the treatment of inflammatory diseases. Its anti-inflammatory effect makes it suitable for the development of biomimetic innovative strategies aiming at modulating stem cells behavior toward a pro-regenerative phenotype in case of injury or inflammation. Here we propose collagen type I meshes fabricated by solvent casting and further cross-linked with HS (Col-HS) to create a biomimetic environment resembling the extracellular matrix of soft tissue. Col-HS meshes were tested for their capability to provide physical support to stem cells growth, maintain their phenotypes and immunosuppressive potential following inflammation. HS-Col effect on stem cells was investigated in standard conditions as well as in an inflammatory environment recapitulated in vitro through a mix of pro-inflammatory cytokines (TNFα and IFNγ; 20ng/ml). A significant increase in the production of molecules associated with immunosuppression was demonstrated in response to the material and when cells were grown in presence of pro-inflammatory stimuli, compared to bare collagen membranes (Col), leading to a greater inhibitory potential when MSC were exposed to stimulated peripheral blood mononuclear cells. Our data suggest that the presence of HS is able to activate the molecular machinery responsible for the release of anti-inflammatory cytokines, potentially leading to a faster resolution of inflammation.